Counteracting effects of a non‐native prey on the demography of a native predator culminate in positive population growth. Issue 7 (2nd September 2016) - Cattau, Christopher E.; Fletcher, Robert J.; Reichert, Brian E.; Kitchens, Wiley M.
Abstract: Identifying impacts of non‐native species on native populations is central to conservation and ecology. While effects of non‐native predators on native prey populations have recently received much attention, impacts of introduced prey on native predator populations are less understood. Non‐native prey can influence predator behavior and demography through direct and indirect pathways, yet quantitative assessments of the relative impacts of multiple, potentially counteracting, effects on native predator population growth remain scarce. Using ≈20 years of range‐wide monitoring data, we tested for effects of a recently introduced, rapidly spreading non‐native prey species ( Pomacea maculata ) on the behavior and demography of the endangered Snail Kite ( Rostrhamus sociabilis ). Previous studies found that food‐handling difficulties caused by the large size of P. maculata (relative to the native P. paludosa ) can lead to energetic deficiencies in juvenile kites, suggesting the potential for evolutionary traps to occur. However, high densities of P. maculata populations could facilitate kites by providing supplemental food resources. Contrary to prior hypotheses, we found that juvenile apparent survival increased ≈50% in wetlands invaded by non‐native snails. Breeding rates and number of young fledged/successful nests were also positively associated with non‐native snail presence, suggesting direct trophic benefits to kites. We found no direct effects of the invasive snail on adult survival or daily nest survival rates. Kite movements and breeding distribution closely tracked the spread of non‐native snail populations. Since 2005, kites have been heavily concentrated in northern regions where non‐native snails have established. This geographic shift has had hidden costs, as use of northern regions is associated with lower adult survival. Despite negative impacts to this key vital rate, matrix population modeling indicated that the multifarious effects of the non‐native snail invasion on kites culminated in increased population growth rates, likely lowering short‐term extinction risks. Results suggest that considering only particular components of behavior or demography may be inadequate to infer the population‐dynamic importance of non‐native prey on native predators, including their role in creating potential evolutionary traps. Our findings provide information pertinent to Everglades restoration, highlighting potential management trade‐offs for non‐native species that may aid imperiled species recovery yet disrupt other native communities.